2016
DOI: 10.1016/j.ijrobp.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

IDEAL-CRT: A Phase 1/2 Trial of Isotoxic Dose-Escalated Radiation Therapy and Concurrent Chemotherapy in Patients With Stage II/III Non-Small Cell Lung Cancer

Abstract: PurposeTo report toxicity and early survival data for IDEAL-CRT, a trial of dose-escalated concurrent chemoradiotherapy (CRT) for non-small cell lung cancer.Patients and MethodsPatients received tumor doses of 63 to 73 Gy in 30 once-daily fractions over 6 weeks with 2 concurrent cycles of cisplatin and vinorelbine. They were assigned to 1 of 2 groups according to esophageal dose. In group 1, tumor doses were determined by an experimental constraint on maximum esophageal dose, which was escalated following a 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…In this study the median survival was 24.3 months in the concurrent setting compared to 18.4 months in the sequential arm and there has been much interest and progress in combining other modified fractionation regimens with cytotoxic chemotherapy [18,19] Potential therapeutic targets to enhance radiotherapy effectiveness.…”
Section: Introductionmentioning
confidence: 85%
“…In this study the median survival was 24.3 months in the concurrent setting compared to 18.4 months in the sequential arm and there has been much interest and progress in combining other modified fractionation regimens with cytotoxic chemotherapy [18,19] Potential therapeutic targets to enhance radiotherapy effectiveness.…”
Section: Introductionmentioning
confidence: 85%
“…As a result, the findings were evaluated in a qualitative manner. 19 relevant publications were identified (Figure1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Search Strategy Methodologymentioning
confidence: 99%
“…Following the establishment of feasibility, prospective clinical trials were implemented to evaluate the use of personalised prescriptions in a patient population. Five prospective clinical trials [19][20][21][22][23] were identified that utilised isotoxic treatment planning techniques to individually prescribe RT for LA-NSCLC. Findings from these five trials are summarised in Table 2.…”
Section: Clinical Evidence For Personalised Radiotherapy Prescriptionsmentioning
confidence: 99%
See 2 more Smart Citations